Spirolactone-type and enmein-type derivatives as potential anti-cancer agents derived from oridonin. (15th October 2022) - Ni, Xiang; He, Chen; Jia, Yilin; Wu, Xiuyuan; Zhou, Kunyu; Xu, Shengtao; Xu, Jinyi; Yao, Hong
Graphical abstract: Highlights: Novel spirolactone- and enmein-type derivatives were obtained from oridonin by simple chemical conversions. The optimal compound was 10-fold more potent than oridonin in K562 cells. The optimal compound showed better cytotoxicity selectivity than oridonin in vitro. The optimal compound significantly suppressed tumor cell proliferation by arresting cell cycle and inducing apoptosis. Abstract: Natural products (NPs) are always the important sources in the field of drug discovery, among which spirolactone-type and enmein-type compounds exhibit a wide range of biological activities, especially anti-tumor activity. Based on previous studies, the spirolactone-type and enmein-type compounds could be derived from natural oridonin (1 ) by several chemical reactions. Herein, a series of novel spirolactone-type and enmein-type derivatives with different aryl allyl ester substitutions at their C-14 hydroxyl group were designed and synthesized. The anti-tumor activity results showed that most of the compounds exhibited better anti-proliferative activities than parent compound oridonin, and the most potent compound had an IC50 value of 0.40 μM in K562 cells. Further mechanistic studies revealed that the optimal compound could arrest K562 cells at G2/M phase by inhibiting cdc-2, cdc-25c and cyclin B1 expression. In addition, the optimal compound induced apoptosis in K562 cells through increasing ROS production and depolarizing mitochondrial membrane potential. Collectively, these valuable results suggested that the most potent compound could be an anti-tumor agent candidate and is worthy of further investigation.